2009
DOI: 10.1128/aac.01619-08
|View full text |Cite
|
Sign up to set email alerts
|

Antistaphylococcal Activity of Dihydrophthalazine Antifolates, a Family of Novel Antibacterial Drugs

Abstract: For a panel of 153 Staphylococcus aureus clinical isolates (including 13 vancomycin-intermediate or heterogeneous vancomycin-intermediate and 4 vancomycin-resistant strains), MIC 50 s and MIC 90 s of three novel dihydrophthalazine antifolates, BAL0030543, BAL0030544, and BAL0030545, were 0.03 and 0.25 g/ml, respectively, for methicillin-susceptible strains and 0.03 and <0.25 g/ml, respectively, for methicillin-resistant strains. For a panel of 160 coagulase-negative staphylococci (including 5 vancomycin-inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 35 publications
3
9
0
Order By: Relevance
“…The impact of the F98Y mutation on (R)-RAB1 is consistent with recent observations with related phthalazine-based DHFR inhibitors, such as BAL0030543 (Fig. 2B) (7,9). While the three-dimensional structures with the BAL compounds are not known, they may use a similar binding mode such that the phthalazine group follows the path of RAB1 form 1, while the pyrimidine moiety extending from the phthalazine would occupy the same position as RAB1 form 2.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The impact of the F98Y mutation on (R)-RAB1 is consistent with recent observations with related phthalazine-based DHFR inhibitors, such as BAL0030543 (Fig. 2B) (7,9). While the three-dimensional structures with the BAL compounds are not known, they may use a similar binding mode such that the phthalazine group follows the path of RAB1 form 1, while the pyrimidine moiety extending from the phthalazine would occupy the same position as RAB1 form 2.…”
Section: Discussionsupporting
confidence: 71%
“…Concomitant with the current work, the broad-spectrum activities of related RAB1-like molecules have been demonstrated by Basilea Pharmaceutica International AG. These studies also highlighted the difficulty in generating spontaneous resistant mu-tations of chromosomal DHFR to inhibitors in the dihydrophthalazine series (7,9).…”
mentioning
confidence: 99%
“…Such mechanisms have been described in other bacterial species (56). Selection of linezolid-resistant mutants in S. aureus and E. faecalis strains has been demonstrated previously (12,37,39), and in the present study a similar propensity to select resistant clones was observed. A resistance mechanism to linezolid in S. aureus and E. faecalis has been described before and involves mutation in the central loop of domain V of the 23S rRNA (G 2576 T was the most common substitution), with the level of resistance depending on the number of mutated 23S rRNA copies.…”
Section: Discussionsupporting
confidence: 71%
“…Vancomycin has been used as a comparator in a significant number of multipassage studies (3,4,6,7,20,21), and the emergence of resistance has been reported in only one of these (3). In our study, the initial MIC for vancomycin increased Ͼ4-fold in two of the four strains tested.…”
Section: Discussionmentioning
confidence: 99%
“…The topical antibiotics mupirocin, fusidic acid, and retapamulin were selected as direct comparators to XF-73, and vancomycin, which has been previously demonstrated to be refractive to the emergence of mutational resistance in multipassage studies (3,6,7,20,21), was also in-cluded. As the mechanism of action (MOA) of daptomycin (16,30) is also proposed to act on the bacterial membrane, it was also tested against USA300, and molecular genetic studies to characterize the mechanism(s) of daptomycin resistance in isolated clones were also undertaken.…”
mentioning
confidence: 99%